2010
DOI: 10.1007/s12665-010-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal enrichment of soil in Sarcheshmeh copper complex, Kerman, Iran

Abstract: Copper smelting and toxic emissions in Sarcheshmeh Copper Complex have resulted in soil pollution especially in the vicinity of the smelting plant. Calculated geoaccumulation index, contamination factor (C f ), and contamination degree (C deg ) indicate surface soil enrichment in potentially toxic metals (As, Cu, Pb, Zn, Mo, and Cd). The results also indicate that most contaminated areas are located in the prevailing wind directions (N and NE). However, continuous copper smelting can result in extensive pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 31 publications
(35 reference statements)
2
28
0
2
Order By: Relevance
“…3.4.1. Columns of 1 to 4 DU are measured above the smelters of Sar Cheshmeh copper complex (Rastmanesh et al, 2010(Rastmanesh et al, , 2011. Emissions of oil industries located on the Khark Island (Ardestani and Shafie-Pour, 2009;Fioletov et al, 2013) are also observed, with columns around 1 to 2 DU.…”
Section: Global Distributionsmentioning
confidence: 93%
“…3.4.1. Columns of 1 to 4 DU are measured above the smelters of Sar Cheshmeh copper complex (Rastmanesh et al, 2010(Rastmanesh et al, , 2011. Emissions of oil industries located on the Khark Island (Ardestani and Shafie-Pour, 2009;Fioletov et al, 2013) are also observed, with columns around 1 to 2 DU.…”
Section: Global Distributionsmentioning
confidence: 93%
“…The results obtained were used to determine the Contamination Factor (CF), degree of contamination (Cdeg), Enrichment Factor (EF) and geoaccumulation Index (Igeo) of the metals in the studied environment. To assess the level of heavy metals contamination in gold mining sites and surroundings, CF and Cdeg were calculated using the method presented by Rastmanesh et al (2010). This method is commonly used by numerous researchers as an indicator of contamination in sediments and soils (Ghadimi, 2014;Banu et al, 2013;Iqbal et al, 2013;Abhijit and Ramkrishna, 2017).…”
Section: Data Processingmentioning
confidence: 99%
“…In the present study the average Upper Continental Crust (UCC) was used (Taylor and Mclennan, 1985;Esser and Turekian, 1993;Jochum et al, 1993). C x F is defined according to four categories given as follows: <1 = low contamination factor, 1-3 = moderate contamination factors, 3-6 = considerable contamination factors and> 6 = very high contamination factor (Rastmanesh et al, 2010;Likuku et al, 2013;Sadhu et al, 2012).…”
Section: Data Processingmentioning
confidence: 99%
“…This could be tantamount to their bioavailability considering the conclusion of Ma & Rao (1997). Rastmanesh et al, (2010) has expressed that residual fraction constitutes a significant proportion for all elements. Kaasalainen & Yli-Halla (2003), the proportion of the residual fraction reflects native metal concentration in soil.…”
Section: Bioavamentioning
confidence: 99%